Two new species of Ardisia subgenus Tetrardisia (Primulaceae-Myrsinoideae) from Borneo - Avelinah Julius; Tadashi Kajita; Timothy M. A. Utteridge (PhytoKeys, 2020)
Ardisia argentiana and A. nagaensis from subgenus Tetrardisia are herein described and illustrated as new species. They are endemic to Borneo and the Indonesian province of Central Kalimantan and to the Malaysian state of Sarawak, respectively. Ardisia argentiana is unique in its linear-oblong leaves, with a long, acuminate-caudate apex, and finely serrulate margins, while A. nagaensis can be easily recognized by its elliptic-lanceolate leaves.